Personalized Nursing Care in Precision-Medicine Era - Luís Carlos Lopes-Júnior RN, OCN, MSc, PhD (SAGE Publishing, 2021)
The extensive investment and development of research in molecular biology in the last decades, mainly after the completion of the Human Genome Project, has raised many expectations regarding its impact on Precision-Medicine Era. To meet the new demands for care, it is necessary that the omics sciences be integrated into nursing practice, especially in nursing care. Based on knowledge of structural genomics, it has been improved techniques that enabled the advancement of research related to functional genomics, which together comprising the "omics" sciences including the transcriptomics, proteomics, the epigenomics and metabolomics. The current challenge is to transform this expanded set of information into clinical benefits for patients, through more accurate diagnoses, treatments, and personalized care to the particularities of individuals and communities. For Nursing, the main challenge is the incorporation of the omics sciences in training and professional practice, so that nurses can safely, scientifically, and autonomously empower themselves to provide personalized care to individuals and families based on Precision-Medicine Era. In this paper, a debate on the impacts and challenges for Nursing to incorporate the Precision-Medicine into clinical practice is described.